High-fat diet decreases activity of the oxidative phosphorylation complexes and causes nonalcoholic steatohepatitis in mice - Inmaculada García-Ruiz; Pablo Solís-Muñoz; Daniel Fernández-Moreira; Montserrat Grau; Francisco Colina; Teresa Muñoz-Yagüe; José A. Solís-Herruzo (The Company of Biologists, 2014)
Nonalcoholic fatty liver disease (NAFLD) is the most frequent histological finding in individuals with abnormal liver-function tests in the Western countries. In previous studies, we have shown that oxidative phosphorylation (OXPHOS) is decreased in individuals with NAFLD, but the cause of this mitochondrial dysfunction remains uncertain. The aims of this study were to determine whether feeding mice a high-fat diet (HFD) induces any change in the activity of OXPHOS, and to investigate the mechanisms involved in the pathogenesis of this defect. To that end, 30 mice were distributed between five groups: control mice fed a standard diet, and mice on a HFD and treated with saline solution, melatonin (an antioxidant), MnTBAP (a superoxide dismutase analog) or uric acid (a scavenger of peroxynitrite) for 28 weeks intraperitoneously. In the liver of these mice, we studied histology, activity and assembly of OXPHOS complexes, levels of subunits of these complexes, gene expression of these subunits, oxidative and nitrosative stress, and oxidative DNA damage. In HFD-fed mice, we found nonalcoholic steatohepatitis, increased gene expression of TNFα, IFNγ, MCP-1, caspase-3, TGFβ1 and collagen α1(I), and increased levels of 3-tyrosine nitrated proteins. The activity and assembly of all OXPHOS complexes was decreased to about 50-60%. The amount of all studied OXPHOS subunits was markedly decreased, particularly the mitochondrial-DNA-encoded subunits. Gene expression of mitochondrial-DNA-encoded subunits was decreased to about 60% of control. There was oxidative damage to mitochondrial DNA but not to genomic DNA. Treatment of HFD-fed mice with melatonin, MnTBAP or uric acid prevented all changes observed in untreated HFD-fed mice. We conclude that a HFD decreased OXPHOS enzymatic activity owing to a decreased amount of fully assembled complexes caused by a reduced synthesis of their subunits. Antioxidants and antiperoxynitrites prevented all of these changes, suggesting that nitro-oxidative stress played a key role in the pathogenesis of these alterations. Treatment with these agents might prevent the development of NAFLD in humans.